PENGARUH KEADILAN DISTRIBUTIF DAN PROSEDURAL TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Pegawai Palang Merah Indonesia Eks Karesidenan Surakarta) - SUHARYOKO SUHARYOKO (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2016)
The purpose of this study is as follows: (1) measure and examine the effect of procedural and dsitributif justice on job satisfaction of employees (2) To measure and examine the effect of job satisfaction on employee performance (3) measure and examine the mediating effect of job satisfaction in influencing procedural justice and distributive justice on employee performance. This research was conducted on PMI Ex-Surakarta Residencies consisting of PMI Surakarta, PMI Sragen, PMI Karanganyar, PMI Wonogiri, PMI Klaten and PMI Boyolali. The population in this study were employees support personnel consisting of as many as 184 employees of non-health and specialty pharmacy employees 20 people. Determination of the number of samples using the formula Slovin and gained as much as 67 samples. As for sampling using proportional random sampling. Problem statement (1) Does procedural and dsitributif effect justice on employee satisfaction? (2) Is the job satisfaction influence on employee performance? (3) Is the mediating effect of job satisfaction procedural and distributive justice on employee performance? The research results been recorded that procedural and distributive justice in PMI Ex-Surakarta Residencies have influence on employee satisfaction. Job satisfaction influence on employee performance. There is a complete mediating effect (full mediation) from employee satisfaction to procedural justice in influencing the performance of employees, and there is a partial mediating effect of job satisfaction against distributive justice in influencing employee performance PMI Ex-Surakarta Residencies. Keywords: procedural, and distributive justice, job satisfaction, performance employee.